Ambient light adaptive LED light dimmer - Taufik Taufik; William Xiong; Jonathan Sato; Saidah Saidah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
This paper presents the design of an Adaptive Light Dimmer based on the method of sensingambient light content to adjust lamp's light intensity accordingly, and thus regulating the room's light content. The device is designed to work with renewable energy sources such as wind and solar energy. This would be useful in less developed countries where AC electricity is not well spread and renewable DC sources, such as solar, can be better utilized. It functions by using the TSL2561 light sensor, ATTiny85 microcontroller to output PWM to the LED driver, LT3795 LED driver to output current to an LED and LT3014 LDO to lower the input voltage and power the microcontroller and sensor. The dimmer is designed to work with a 48V input voltage and operate from an input light range of 20 to 100 Lux. Above 100 Lux the light is off and below 20 Lux the light is fully on.